1986
DOI: 10.1161/01.hyp.8.5.422
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of deranged sodium homeostasis in essential hypertension.

Abstract: SUMMARY Essential hypertension is thought to produce a uniform exaggerated natriuresis and diuresis. Because validation of this formulation in humans is incomplete, the natriuretic and diuretic responses to acute volume expansion were characterized by using water immersion to the neck. This method provides a volume stimulus identical to that induced by 2 L of saline without plasma compositional change. Twenty-seven subjects with essential hypertension were studied on three occasions in the seated posture while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…This was associated with an elevated arterial pressure (∼ 10-15 mmHg) in the uni-x animals. Dissociation between diuresis and natriuresis has been reported in humans following volume expansion induced by head-out water immersion and maybe associated with the degree of central hypervolaemia achieved necessary for vasopressin suppression [30]. This suggests that the remnant kidney has a poor capacity to tightly and rapidly regulate sodium and water balance.…”
Section: Discussionmentioning
confidence: 99%
“…This was associated with an elevated arterial pressure (∼ 10-15 mmHg) in the uni-x animals. Dissociation between diuresis and natriuresis has been reported in humans following volume expansion induced by head-out water immersion and maybe associated with the degree of central hypervolaemia achieved necessary for vasopressin suppression [30]. This suggests that the remnant kidney has a poor capacity to tightly and rapidly regulate sodium and water balance.…”
Section: Discussionmentioning
confidence: 99%
“…33 " 35 More recent investigations have demonstrated a heterogeneity in sodium excretion rates after saline loads in hypertensive patients. 36 Rydstedt et al 37 studied sodium excretion rates after saline infusion in hypertensive individuals grouped by before sodiumloading renin levels. Those with normal renin hypertension had a blunted rate of sodium excretion after a saline load.…”
Section: -29mentioning
confidence: 99%
“…Our data permit a better analysis of the nonspecific (volume-induced) changes in urinary calcium excretion of hy pertensive humans [4], Wl studies were performed in 41 essen tial hypertensive subjects; they consumed a controlled diet containing 180 mmol sodium/day and 25 mmol calcium/day. As pre viously described by Epstein et al [5], WIinduced central hypervolemia identified two distinct populations with a markedly differ ent natriuretic response. Twenty-nine pa tients exhibited a significant diuretic re sponse (p < 0.001) and either appropriate or exaggerated natriuresis (from 121 ± 11 to 330 ± 24 pmol/min.…”
mentioning
confidence: 60%